Probing Experiential Learning Approach Effect on Critical Thinking Ability of Secondary School Students' in Biology - Nwuba, Izunna; OSUAFOR, Abigail Mgboyibo; EGWU, Sussan Onyebuchi; OBIKEZIE, Maxwell Chukwunazo (International Journal of Research in STEM Education, 2024)
The study explored effect of Experiential Learning Approach (ELA) on secondary school students’ CTA in biology. The study is quasi-experimental, adopting the non-randomized control group design. 4755 senior secondary year 2 (SS2) students constituted the population. Multi-stage sampling procedure was employed to compose the sample size of 53 SS2 students. The sampled students who were in two intact classes were randomly assigned to experimental and control groups. Adapted Watson-Glaser Critical thinking appraisal (WGCTA) validated by experts with a reliability coefficient of 0.71 was used for data collection. Mean and SD were used in answering the research questions and ANCOVA to test the null hypotheses. Findings revealed that ELA enhanced students’ CTA in biology, irrespective of gender, more than CLM. As a result, the study concluded that ELA is a gender-inclusive strategy that improves students' CTA and then recommended that biology teachers should adopt ELA in classrooms to improve students’ CTA.